Inconsistent Effect of Arousal on Early Auditory Perception - Bolders, Anna C.; Band, Guido P. H.; Stallen, Pieter Jan M. (Frontiers in Psychology, 2017)
Mood has been shown to influence cognitive performance. However, little is known about the influence of mood on sensory processing, specifically in the auditory domain. With the current study we sought to investigate how auditory processing of neutral sounds is affected by the mood state of the listener. This was tested in two experiments by measuring masked auditory detection thresholds before and after a standard mood-induction procedure. In the first experiment (N = 76) mood was induced by imagining a mood-appropriate event combined with listening to mood inducing music. In the second experiment (N = 80) imagining was combined with affective picture viewing to exclude any possibility of confounding the results by acoustic properties of the music. In both experiments the thresholds were determined by means of an adaptive staircase tracking method in a two-interval forced-choice task. Masked detection thresholds were compared between participants in four different moods (calm, happy, sad, anxious), which enabled differentiation of mood effects along the dimensions arousal and pleasure. Results of the two experiments were analyzed both in separate and in a combined analysis. The first experiment showed that, while there was no impact of pleasure level on the masked threshold, lower arousal was associated with lower threshold (higher masked sensitivity). However, as indicated by an interaction effect between experiment and arousal, arousal did have a different effect on the threshold in experiment 2. Experiment 2 showed a trend of arousal in opposite direction. These results show that the effect of arousal on auditory masked sensitivity may depend on the modality of the mood inducing stimuli. As clear conclusions regarding the genuineness of the arousal effect on the masked threshold cannot be drawn, suggestions for further research that could clarify this issue are provided.